Acetylator Status Among Newly Diagnosed and Recurrent Tuberculosis Patients from Kupang, Eastern Part of Indonesia - Sahiratmadja E; Rini IA; Penggoam S; Charles A; Maskoen AM; Parwati I (Dove Medical Press, 2021)
Edhyana Sahiratmadja,1 Ika Agus Rini,2 Simeon Penggoam,3 Afandi Charles,2 Ani Melani Maskoen,1,2 Ida Parwati4 1Division of Biochemistry and Molecular Biology, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 2Health Research Unit, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 3Laboratorium Mikrobiologi, RSUD Prof. Dr. WZ Johannes, Kupang, Indonesia; 4Department of Clinical Pathology, Faculty of Medicine, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Edhyana SahiratmadjaDivision of Biochemistry and Molecular Biology, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jl. Raya Bandung – Sumedang KM 21, Jatinangor, Sumedang, Jawa Barat, 45363, IndonesiaTel +62 22 779 5594Fax +62 22 779 5595Email e.sahiratmadja@unpad.ac.idPurpose: N-acetyltransferase-2 enzyme in the liver, encoded by NAT2 gene, plays a central role in metabolizing tuberculosis (TB) drug isoniazid (INH). Low compliance of patients toward six-month TB therapy and internal host factors, ie comorbid diseases, immune status, and genetic profiles, are factors leading to treatment failure and recurrence of pulmonary TB infection. This study aimed to explore the NAT2 acetylator status among newly diagnosed and recurrent pulmonary TB patients in eastern part of Indonesia.Patients and Methods: Archived DNA of TB patients (n=124) and healthy controls (n=124) were sequenced, and NAT2 acetylator status was determined, then categorized as fast, intermediate, or slow acetylators. Pulmonary TB patients who had no previous TB treatment history were designated as newly diagnosed pulmonary TB, whereas patients with a history of TB treatment were designated as recurrent pulmonary TB. The demographic, clinical, and microbiological data between pulmonary TB groups were compared, and acetylator status was described among groups.Results: Male was more significantly prevalent in the recurrent pulmonary TB group (p=0.025), and anemia was more prevalent in new pulmonary TB (p=0.003). The acetylator status in pulmonary TB patients compared to healthy controls were rapid (33.9% vs 48.1%), intermediate (57.8% vs 33.0%), and slow acetylators (8.3% vs 18.9%), respectively. Interestingly, the rapid and intermediate acetylator were significantly more prevalent in pulmonary TB patients than in healthy controls (p=0.023, OR=2.58 (1.12– 5.97). Furthermore, no differences were found in acetylator status between new and recurrent pulmonary (p=0.776).Conclusion: Rapid and intermediate acetylators status predominated the pulmonary TB patients in Kupang, eastern part of Indonesia, postulating different genetic makeup in this area. As the pulmonary TB patients in Kupang exhibit more rapid acetylator phenotype, the acetylator status might be relevant to be checked before TB therapy for adjusting treatment dose to prevent drug resistances.Keywords: acetylator status, NAT2, Indonesia, tuberculosis, recurrence